Identify Function of WASL in Prognosis of Cervical Cancer Based on Omics Data - Hou, Jinxuan; Chen, Chen; Hu, Yingying; Gong, Qing; Gan, Lijuan; Xu, Yu (Frontiers in Cell and Developmental Biology, 2021)
Objective To clarify the clinical relevance of WASP like actin nucleation promoting factor (WASL) in patients with cervical cancer and associated mechanisms. Methods and materials We obtained high prediction accuracy and determined the correlation between the expression of WASL and the clinical characteristics of cervical cancer patients. Differentially expressed genes (DEGs) were identified using microarray. Gene ontology (GO) enrichment analysis and gene set enrichment analysis (GSEA) were performed to determine potentially relevant mechanisms related to the prognostication ability of WASL expression. Results Chi-square test and multivariable logistic regression analysis suggested that lower expression of WASL was associated with lower pathological stage (Chi-square test: P=0.022, Chi-square=9.613; logistic regression: OR=0.869, 95% CI: 0.756-0.991, P=0.041). Patients in the WASL high expression group have worse OS (HR: 0.555, 95% CI: 0.348-0.884, log-rank P=0.012) and RFS (HR=0.449, 95% CI: 0.215-0.934, log-rank P=0.028) compared with those in the WASL low expression group. Univariate and multivariable Cox proportional hazards regression model suggested that WASL expression was an independent prognostic factor for predicting overall survival and recurrence free survival in cervical cancer. DEGs were mostly enriched GO terms related to DNA replication or the proliferation of tumor cells. The results of GSEA suggested samples in the WASL knockdown group were enriched in glycolysis, TNF-α signaling via NFkB, mTORC1 signaling, and Wnt/β-catenin signaling. Conclusions WASL expression was associated with the pathological stage, and it might be an independent prognostication factor in patients with cervical cancer. Knockdown of WASL might be correlated with biological processes such as glycolysis, TNFα signaling, mTOR signaling, and Wnt/β-catenin signaling.